Mycobacterium tuberculosis infection and diabetes mellitus-mycobacterium tuberculosis dual burden in subjects attending infectious diseases hospital Calabar, Nigeria - Eworo, Raymond E.; Okhormhe, Zibril A.; Ntamu, Ntamu A.; Esiere, Kaiso-Umo S. (International Journal of Research in Medical Sciences, 2019)
Background: The rising global DM epidemic is driving the problem of TB control. This research determined glycemic control in TB only infected and DM-TB comorbidity and the consequence of the double burden on treatment outcome. Methods: fifty M. TB infected subjects and fifty control subjects were enrolled into the study, all the participants gave consents. FPG and HbA1c were determined by Colorimetry. Data were analyzed using SPSS version 20.0 statistical package, differences between groups and variation among groups were determined by Student’s t-test and ANOVA respectively while the association between variables by Pearson’s correlation. Differences were considered statistically significant at p<0.05. Results: The mean FPG and HbA1c levels of TB subjects were significantly (P<0.05) higher than those of the control. The mean BMI of the TB infected subjects was significantly lower (p=0.001) than that of the controls. The mean age, FPG and HbA1c of TB subjects at the beginning phase of treatment were significantly lower (p<0.05) than those of subjects at the continuation phase of treatment. The mean age, FPG and HbA1c of subjects with DM-M.TB coexistence were significantly (p<0.05) higher than those of the M.TB only infected subjects. BMI of the DM-M.TB comorbidity subjects was lower than that of the M.TB only infected subjects (p=0.109). A significant positive correlation was obtained between HbA1C and FPG in M.tb infected subjects. (r=0.910, p=0.001). A negative correlation obtained between HbA1C and BMI in M.tb infected subjects. (r=0.267, p=0.061). Conclusion: Infection with mycobacterium tuberculosis poses a risk to DM and vice versa, which may adversely affect treatment outcome and control of both diseases. Firm efforts to control DM may likely have a significant valuable effect on TB treatment outcome.